No difference in the frequency of locus-specific methylation in the peripheral blood DNA of women diagnosed with breast cancer and age-matched controls. (December 2011) - Wojdacz, Tomasz K; Thestrup, Britta B; Cold, Søren; Overgaard, Jens; Hansen, Lise L
There is no doubt that aberrant somatic (tumor-specific) methylation significantly contributes to the carcinogenic process. However, the question of the relevance of methylation pattern changes, acquired by individuals during their development and lifetime or inherited through the germline, to the pathology of different diseases, remains open. Recently, a number of studies addressed the question of the prevalence of aberrant methylation of cancer-related genes in peripheral blood leukocyte (PBL) DNA and indicated a strong possibility that the presence of constitutional methylation of different genes might predispose for cancer development. Here, we have used the methlyation-sensitive high-resolution melting approach to examine the methylation status of the BRCA1, BRCA2, APC, RASSF1A and RAR ββ 2 genes in PBLs of a group of women diagnosed with breast cancer, and an age-matched control group with no signs of breast cancer. No significant differences in the frequency of methylation of the above genes were found between cases and controls in our study. Hence, testing for the presence of methylation of cancer-related genes in PBL DNA from women diagnosed with sporadic breast cancer and classified for testing without any pathological or clinical selection criteria does not seem to have clinical applicability.